The Impact of Identity Politics in the 2017 DKI Elections on Anies' Electability Ahead of the 2024 Presidential Election - Dealina Susilowati, (Program Studi Pendidikan Administrasi Perkantoran FIS UNM Kampus UNM Gunungsari Baru Makassar, 2024)
Indonesia is a heterogeneous country with a population that has different backgrounds, making it vulnerable to political identity. Identity politics is often an issue that attracts the attention of the public, one of which occurred in the DKI Jakarta elections in 2017. Anies, who is running for president in the 2024 election, certainly expects great support from the people of DKI Jakarta, as the community he once led. However, Anies could not escape the turmoil of identity politics in the 2017 elections. The level of electability of a prospective leader is considered important to gain vote support from the public. Researchers used the theory of identity politics and electability to determine indicators in this study. This study aims to determine whether there is an influence of identity politics in the 2017 DKI Jakarta elections on Anies' electability ahead of the 2024 presidential election. The population of this study is the people of DKI Jakarta with millennial age. The sample taken was 100 people using the Slovin formula. The method used in this research is quantitative in the form of a questionnaire. Data analysis was carried out with the IBM SPSS version 24 program. This study shows that all variables meet the validity criteria. The novelty of this research is that it examines the variables of identity politics and electability which produce data in the form of statistical figures. This study found that the identity politics of the 2017 DKI Jakarta elections had an effect on Anies' electability ahead of the 2024 presidential election.